MBKM Implementation and Its Influence on Graduate Competence at State Islamic Higher Education Institutions - Saiful; Silahuddin; Fadhilah, Raihan (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
The Indonesian government launched the Merdeka Belajar Kampus Merdeka (MBKM) program that offers students diverse learning opportunities beyond the classroom. This study aims to investigate the implementation of the MBKM program in State Islamic Higher Education Institutions in Aceh. The study utilized a qualitative case study research method, conducted at three PTKINs in Aceh. It involved UIN Ar-Raniry Banda Aceh, IAIN Lhokseumawe, and IAIN Langsa. Data were collected through observations and interviews and then analyzed using thematic analysis. Findings reveal that implementing the MBKM program includes curriculum integration, experiential learning, student mobility, community service, research, and digital platforms. Efforts to achieve these involve partnerships, curriculum reform, digital innovation, faculty capacity building, experiential learning, and a quality assurance mechanism. Further, the success factors comprise institutional synergy, effective socialization, well-defined policies, adequate resource allocation, and student motivation. Conversely, the implementation faces challenges such as insufficient data reporting and inconsistent credit recognition. Given the study’s limited scope, future studies should broaden their focus to enhance generalizability and explore institution-specific challenges in greater depth.